Thermal stability improvement of a multiple finger power SiGe heterojunction bipolar transistor under different power dissipations using non-uniform finger spacing - 陈亮 张万荣 金冬月 沈佩 谢红云 丁春宝 肖盈 孙博韬 王任卿 (Chinese physics B, 2011)
A method of non-uniform finger spacing is proposed to enhance thermal stability of a multiple finger power SiGe heterojunction bipolar transistor under different power dissipations. Temperature distribution on the emitter fingers of a multi-finger SiGe heterojunction bipolar transistor is studied using a numerical electro-thermal model. The results show that the SiGe heterojunction bipolar transistor with non-uniform finger spacing has a small temperature difference between fingers compared with a traditional uniform finger spacing heterojunction bipolar transistor at the same power dissipation. What is most important is that the ability to improve temperature non-uniformity is not weakened as power dissipation increases. So the method of non-uniform finger spacing is very effective in enhancing the thermal stability and the power handing capability of power device. Experimental results verify our conclusions.